The Impact of Self-Efficacy on Performance Employee: Study of Literature - Rajendra Dwi Maheswara; Nuha Aliyah; Fatahillah Ayatulloh Khomeini (International Conference on Psychology and Education (ICPE), 2023)
Self-efficacy is an individual's self-confidence or belief in their ability to do something, produce something, organize, achieve their goals, and also implement actions to realize certain skills. A person's self-efficacy will usually influence the individual in determining an action or decision. Where the action is carried out to achieve a goal or several things or possibilities that will be present in the future. The purpose of this research is to find out the effect of self-efficacy on employee performance. The research method used is qualitative with a literacy review approach through the selection of keywords namely "organization", "self-efficacy", and "employee performance". Based on the research that has been done, it can be concluded that the higher the self-efficacy, the better the employee's performance, and vice versa, the lower the self-efficacy, the worse the employee's performance. Self-efficacy is very helpful in realizing better performance. Employees who have high self-efficacy will find it easier to complete a company task and be able to face all obstacles that stand in their way, so that they can improve and help the organization or company achieve its goals.